Purification and synthesis of eosinophilotactic tetrapeptides of human lung tissue: identification as eosinophil chemotactic factor of anaphylaxis. - Goetzl, E J (1975)
Preferential eosinophil chemotactic activity exhibiting a molecular weight comparable to that released from sensitized human lung fragments challenged with specific antigen and designated eosinophil chemotactic factor of anaphylaxis has been isolated from extracts of human lung fragments by sequential purification on Sephadex G-25, Dowex-1, Sephadex G-10, and paper chromatography. Two eosinophilotactic tetrapeptides of amino acid sequence Val-Gly-Ser-Glu and Ala-Gly-Ser-Glu were recovered from the extracts in 4-12% overall yield of the low molecular weight peak from Sephadex G-25. Purified eosinophil chemotactic factor of anaphylaxis and the synthetic tetrapeptides were maximally active in amounts from 0.1 to 1.0 nmol per chemotactic chamber, and the activity was dependent on both the NH2-terminal and the COOH-terminal residues. Both natural and synthetic peptides were preferentially chemotactic for eosinophils and rendered them unresponsive to a subsequent stimulus.